Strange Bedfellows: Jim Jones and the Disciples of Christ - Tyrrell, Kelly (Stone-Campbell journal, 2023)
The socially-progressive ministry of Jim Jones and the explosive growth of the Peoples Temple Christian Church (Disciples of Christ) in the 1960s and 1970s has been largely overshadowed by its tragic ending at the Jonestown Massacre. The story involves the rise and fall of Jones and the Peoples Temple and how Disciples' leadership let them operate autonomously, often praising them as an exemplary local church. However, having ignored warning signs and allegations in the early 1970s, Disciples' leadership was scrutinized afterward for ineffective oversight. The tragic outcome highlights the tension between Disciples' historical commitment to local church autonomy and their systems for covenant accountability.